PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS KVISOFT FLIPBOOK DENGAN MODEL DISCOERY LEARING PADA MATERI ARTHROPODA - Syarifah Hanum Hasibuan; Zulfarina Zulfarina; Riki Apriyandi Putra (saintifika, 2022)
Education is a learning activity that determines the success of achieving student learning outcomes in class. So, to achieve learning objectives by increasing student learning outcomes, it is necessary to have a good and correct learning process with the help of facilities, good learning methods. This study aims to determine whether the development of an interactive e-module based on kvisoft flipbook with the discovery learning model on arthropod material affects student learning outcomes in class X SMA 15 N Pekanbaru. The type of research used is Research & Development research through the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation). The e-module was validated by 5 validators by Riau University lecturers and teachers at SMA N 15 Pekanbaru. The results showed that the quality of the kvisoft flipbook-based interactive e-module with the discovery learning model was very good. the e-module validation results are 3.52 in the very valid category, and the practicality test results are 87.22 in the very practical category